Breadcrumbs - Ursu, Anne.; McGuire, Erin (New York : Walden Pond Press, 2011)
"Hazel and Jack are best friends until an accident with a magical mirror and a run-in with a villainous queen find Hazel on her own, entering an enchanted wood in the hopes of saving Jack's life" -- Provided by publisher.
Ages 8-12.
Accelerated Reader AR
Keywords: Magic mirrors -- Juvenile fiction; Friendship -- Juvenile fiction; Rescues -- Juvenile fiction; Children -- Juvenile fiction; Fantasy fiction